Clinics in diagnostic imaging (205) - Ong, Chern Yue Glen (Singapore Med J, 2020)
A 48-year-old woman presented with chronic right heel pain and paraesthesia over the foot. Magnetic resonance imaging of the right foot demonstrated isolated atrophy of the abductor digiti minimi. A diagnosis of Baxter’s neuropathy was made and the patient was managed successfully via surgical release. We describe the clinical and radiological features of Baxter’s neuropathy and, with brief examples, outline other causes of chronic heel pain.